2017
DOI: 10.1016/j.adro.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Distant intracranial failure in melanoma brain metastases treated with stereotactic radiosurgery in the era of immunotherapy and targeted agents

Abstract: PurposeStereotactic radiosurgery (SRS) in combination with immunotherapy (IMT) or targeted therapy is increasingly being used in the setting of melanoma brain metastases (MBMs). The synergistic properties of combination therapy are not well understood. We compared the distant intracranial failure rates of intact MBMs treated with SRS, SRS + IMT, and SRS + targeted therapy.Methods and materialsCombination therapy was defined as delivery of SRS within 3 months of IMT (anti-CTLA-4 /anti-PD-1 therapy) or targeted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 25 publications
5
42
0
1
Order By: Relevance
“…Our findings indicate that these immune checkpoint inhibitors are effective for controlling not only the primary melanoma but also distant metastases to the brain. Several previous reports have shown a regional immunomodulatory effect and penetration of novel systemic agents into the brain [8,11,12,15,18,20,21,23]. The present results might indicate passage of these agents thorough the bloodbrain barrier in melanoma patients, thereby leading to suppression of new metastases to the brain.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Our findings indicate that these immune checkpoint inhibitors are effective for controlling not only the primary melanoma but also distant metastases to the brain. Several previous reports have shown a regional immunomodulatory effect and penetration of novel systemic agents into the brain [8,11,12,15,18,20,21,23]. The present results might indicate passage of these agents thorough the bloodbrain barrier in melanoma patients, thereby leading to suppression of new metastases to the brain.…”
Section: Discussionsupporting
confidence: 50%
“…Brain metastasis from malignant melanoma occurs at a high incidence of almost 10%, and the rate exceeds 40% in patients with stage 4 disease [1,3,6,7,9,13,14,17,18,20,23,[26][27][28][29]. Single or multimodality therapies including surgical resection, whole-brain radiation therapy, and stereotactic radiosurgery (SRS) are generally performed for brain metastases depending on the systemic condition of the patient.…”
Section: Introductionmentioning
confidence: 99%
“…In total, 346 potentially relevant citations were reviewed (Figure 1). Ultimately, 16 studies published from 2009 to 2019 that reported OS and/or PFS data were included in the final analysis [17,[19][20][21][22][27][28][29][30][31][32][33][34][35][36][37]. The total number of patients included was 4045 ranging from 45 to 1025 patients per study (median, 151).…”
Section: Resultsmentioning
confidence: 99%
“…As compared with wild-type BRAF, BRAF mutation is an independent predictor of better prognosis in patients with melanoma brain metastases receiving SRS (11). On the other hand, the combination of SRS and immune checkpoint inhibitor (ani-PD-1 antibody or anti-CTLA-4 antibody) is also associated with reduction of distant intracranial failures compared with SRS alone or SRS with BRAF inhibitor (12). X-ray irradiation induces PD-L1 expression in mouse cancer cells, but enhances a tumour-suppressing effect in combination with anti-PD-1 antibody (13).…”
Section: Discussionmentioning
confidence: 99%